Enhanced aging properties of HKUST-1 in hydrophobic mixed-matrix membranes for ammonia adsorption. Issue 4 (21st January 2016) - DeCoste, Jared B.; Denny, Jr., Michael S.; Peterson, Gregory W.; Mahle, John J.; Cohen, Seth M.
Abstract : The metal-organic framework (MOF) HKUST-1 incorporated into a mixed-matrix membrane (MMM) exhibits enhanced water stability while maintaining gas removal capabilities commensurate with those of the free powder form. Abstract : Metal–organic frameworks (MOFs) in their free powder form have exhibited superior capacities for many gases when compared to other materials, due to their tailorable functionality and high surface areas. Specifically, the MOF HKUST-1 binds small Lewis bases, such as ammonia, with its coordinatively unsaturated copper sites. We describe here the use of HKUST-1 in mixed-matrix membranes (MMMs) prepared from polyvinylidene difluoride (PVDF) for the removal of ammonia gas. These MMMs exhibit ammonia capacities similar to their hypothetical capacities based on the weight percent of HKUST-1 in each MMM. HKUST-1 in its powder form is unstable toward humid conditions; however, upon exposure to humid environments for prolonged periods of time, the HKUST-1 MMMs exhibit outstanding structural stability, and maintain their ammonia capacity. Overall, this study has achieved all of the critical and combined elements for real-world applications of MOFs: high MOF loadings, fully accessible MOF surfaces, enhanced MOF stabilization, recyclability, mechanical stability, and processability. This study is a critical step in advancing MOFs to a stable, usable, and enabling technology.